The comparison of attitudes of general high school and religion-oriented high school students related with physical education and sport lessons - Emin Kuru; Haci Sahın; Ridvan Ozkan (Selcuk University, 2015)
The objective of this research was to compare the general high school students who received general education and the religion-oriented high school students who received religious education in terms of the attitudes about the physical education and sport course in accordance with the independent variables derived from the students' personal information and their families, and to identify whether there was a meaningful difference between them or not. The population of the research was made of 19245 students receiving education in the general high schools and the religion-oriented high schools at the Yenimahalle district of the Ankara province in the academic year 2009 - 2010. As a data collection means, 5 point likert Physical Education and Sport Attitude Scale developed by Demirhan amp; Altay was used herein. In order to determine if there was any difference in the attitudes of the students t-tests were applied in the statistical processes. For all the statistical estimations, the significance level was regarded to be 0.05. According to the research results; when the measured attitudes of the general high school students and the measured attitudes of the religion-oriented high school students about the physical education and sport course were compared, the statistically meaningful differences were observed between the attitudes of the male students studying at the general high schools and the male students studying at the religion-oriented high schools, between the attitudes of the female students having education at the general high schools and the attitudes of the female students having education at the religion-oriented high schools, between the attitudes of students in the general high schools in terms of their genders, between the attitudes of students in the religion-oriented high schools in terms of their genders, between the gender-based attitudes of all students who were included in the scope of the research, between the learning school type-based attitudes of the students who were individuals doing physical exercise in their family.